Giant Shift Photovoltaic Current in Group V‐V Binary Nanosheets. Issue 4 (24th January 2022) - Kaner, Ngeywo Tolbert; Wei, Yadong; Ying, Tao; Xu, Xiaodong; Li, Weiqi; Raza, Ali; Li, Xingji; Yang, Jianqun; Jiang, YongYuan; Tian, Wei Quan
Abstract: The bulk photovoltaic effect shift current (SC), a constant photocurrent generated by irradiating polar homogeneous non‐centrosymmetric materials has lately emerged as a possible option for next‐generation photovoltaic systems that may potentially overcome the Shockley–Queisser limits. The current work predicts gigantic and anisotropic SC with multiple peaks across a wide range of frequencies in pristine 2D monolayer α‐AsP and α‐NP based on first‐principle calculations. The dominant SC tensors components hosted by 2D monolayer α‐AsP and α‐NP are the in‐plane, and reaches peaks of −154 µАV −2, and 87 µАV −2, respectively, in the UV region. The SC magnitudes of the α‐AsP are not significantly affected by the spin‐orbital coupling, while in α‐NP, no such effect occurs. This study recommends new photovoltaic materials with strong SC peaks spread across the electromagnetic spectrum, largely within the UV region. Abstract : Low dimensional materials have emerged as potential candidates for large shift current (SC), the dominant dc ‐current response in the bulk photovoltaic effect (BPVE). Large in‐plane SC with giant peaks spread across the solar spectrum hosted in single‐layer 2D α‐AsP and α‐NP is elucidated, largely within the UV region, thus can offer improved BPVE performance for optoelectronic applications.